O Brincar Na Formação Do Pedagogo / Professor De Educação Infantil E Dos Anos Iniciais No Estado De São Paulo - Santos, Nathalia Venancio Dos [UNIFESP] (2017)
The Dissertation Has As A Research Theme The Presence Of Content Play In The Training Of Teachers Of Early Childhood Education And Initial Series Of Basic Education Formed In Pedagogy Courses. It Demonstrates That Play Has Been Studied By Different Areas Of Knowledge And Has Stood Out As Essential In Education, Especially With Regard To The Development And Learning Of Children. The Research Aimed To Understand More And Better How The Theme Of Play Appears In The Formal Curriculum Of Pedagogy Courses, Specifically In The State Of São Paulo. Therefore, The Curricula Of The Courses Of Pedagogy In The State Of São Paulo Were Analyzed, In Addition To A Survey At The Capes Bank Of Theses And Dissertations That Mention The Theme Associated With Teacher Education.